The Joint Choice of Retirement Age and Postretirement Hours of Work - Burtless, Gary; Moffitt, Robert A. (Journal of Labor Economics, 1985)
In this paper we develop and estimate the first complete and internally consistent model of the effect of Social Security on the labor supply of the aged. We develop a simple life-cycle model that captures the effect of Social Security on the joint choice of the date of retirement and hours of work immediately after retirement. We show that in the presence of Social Security the budget constraint relating these choices is highly complex and nonlinear, and we develop a maximum likelihood procedure for the model that yields consistent parameter estimates. Our procedure avoids the selectivity biases present in prior studies that have ignored the nonlinearity of the constraint or have examined only self-selected subsamples that exclude nonretirees. Our results show that Social Security has a significant, though relatively small, effect on the age of retirement and postretirement hours of work, and that the effect of Social Security grows with advancing age.